Optimization Of Coffee Grounds and Fly Ash Based Adsorbent Composition with Phosphoric Acid Activator for Tofu Industry Liquid Waste Purification - Mustika Agustini Alfithroh; Khalaida Fania Fattah; Yusup Muhammad Zulfikar; Zakiyyah Tsuroyyaa; Feby Nurghaida Zaharani; Alfiana Adhitasari (Journal of Green Science and Technology, 2025)
The direct disposal of tofu industrial wastewater without treatment can have negative impacts on the environment due to its organic content. One effort that can be done is to process tofu liquid waste using the adsorption method. Nowadays, coffee shops are growing rapidly in indonesia, resulting in a lot of coffee grounds waste which can be used as raw material for activated charcoal because of its carbon content. In addition to coffee grounds, other waste in the form of fly ash is also used as an adsorbent because of its silica content. This study aims to determine the optimization of the composition of coffee grounds and fly ash adsorbents in the purification of tofu industry liquid waste and to determine the optimum contact time so that liquid waste is obtained in accordance with quality standards. Observation parameters include acidity (ph) and chemical oxygen demand (cod). Coffee grounds charcoal is activated using 0.1 n h₃po₄ solution then mixed with fly ash in a ratio of 20:80; 30:70; 50:50; 70:30; and 80:20. The adsorption process is carried out in batches for 60, 90, and 120 minutes. The results of the study showed the optimum composition of the adsorbent 20:80 and contact time 120 minutes with a final cod of 2,761 mg/l, ph 6.21, and a cod reduction of 80.46%.